Crystalline and oxide phases revealed and formed on InSb(111)B - Mäkelä J; Jahanshah Rad ZS; Lehtiö J; Kuzmin M; Punkkinen MPJ; Laukkanen P; Kokko K (NATURE PUBLISHING GROUP, 2022)
Oxidation treatment creating a well-ordered crystalline structure has been shown to provide a major improvement for III–V semiconductor/oxide interfaces in electronics. We present this treatment’s effects on InSb(111)B surface and its electronic properties with scanning tunneling microscopy and spectroscopy. Possibility to oxidize (111)B surface with parameters similar to the ones used for (100) surface is found, indicating a generality of the crystalline oxidation among different crystal planes, crucial for utilization in nanotechnology. The outcome is strongly dependent on surface conditions and remarkably, the (111) plane can oxidize without changes in surface lattice symmetry, or alternatively, resulting in a complex, semicommensurate quasicrystal-like structure. The findings are of major significance for passivation via oxide termination for nano-structured III–V/oxide devices containing several crystal plane surfaces. As a proof-of-principle, we present a procedure where InSb(111)B surface is cleaned by simple HCl-etching, transferred via air, and post-annealed and oxidized in ultrahigh vacuum.